Pengaruh Game Interaktif Wordwall dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadist di Kelas VII MTsS Persatuan Umat Islam Kuningan - Fatimah Az-Zahra; Eva Gustiana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of using interactive game-based learning media Wordwall on increasing student learning motivation in the subject of Al-Qur'an Hadith in class VII MTsS Persatuan Umat Islam (PUI) Kuningan. The study used a quantitative approach with pre-experiment method and One-Group Pretest-Posttest design. The research sample consisted of 30 seventh grade students. The research instrument was a learning motivation questionnaire given before and after treatment. Data analysis was conducted using IBM SPSS Statistics software version 26. The results showed an increase in the average score of learning motivation from 36.13 to 47.37. The Wilcoxon Signed Ranks test resulted in a significance value of 0.000 (p < 0.05), which indicates that the use of Wordwall interactive games has a positive and significant effect on increasing student learning motivation.